FRI0717 Positive conversion of tuberculosis screening results and incidence of active tuberculosis infection in patients receiving biologic treatment. (15th June 2017) - Park, M-C; Kim, HW; Han, SH
Abstract : Background: Previous studies reported active tuberculosis infections can occur during biologic treatment in patients with negative baseline LTBI screening. Current recommendations suggesting the annual testing for latent tuberculosis infections are mainly issued for patients with rheumatoid arthritis (RA) receiving anti-TNF inhibitors and there are lacking evidence for patients receiving non-TNF biologic agents and for patients with ankylosing spondylitis (AS) or psoriatic arthritis (PsA). Objectives: This study was performed to investigate the conversion rate of initially negative tuberculosis screening test results during biologic treatment and the usefulness of repeated screening test for detecting unexpected tuberculosis infection in patients with RA, AS, and PsA. Methods: A total of 95 patients (43 with RA, 50 with AS, and 2 with PsA) who had negative baseline interferon γ releasing assay (IGRA) results, which were assessed using QuatiFERON-TB Gold in tube (QTF-GIT), prior to initiation of biologic treatment were enrolled in this study. All patients received biologic agents for the treatment of their diseases and rescreening with QTF-GIT were performed in all patients after median 12 months from baseline test. Clinical characteristics were compared between converters and non-converters and incidence of active tuberculosis infection was evaluated. Results: Patients were treated with different biologics (23 with etanercept, 50 with adalimumab, 5 with infliximab, 4 with golimumab, 1 with certolizumab pegol, 3 with abatacept, and 9 with tocilizumab). Positive conversions of initially negative IGRA were found in 13 (6 patients with etanercept, 4 patients with adalimumab, 2 patients with tocillizumab and 1 patient with abatacept) of 95 patents (13.7%) after initiation of biologic treatment. Age over 50 years and diagnosis of RA were more common in converters. Multivariate analysis showed that age over 50 was an independent risk factor for IGRA conversion with OR 4.36 (95% CI 1.10 - 17.34, p=0.036). During biologic treatments, active tuberculous infections were found in 3 of 13 converters (23.1%) Conclusions: Although initial screening test showed negative results, the serial follow-up of tuberculosis screening test should be considered during biologic treatment in patients with rheumatic diseases to prevent unexpected tuberculosis infection. References: Hatzara C, Hadziyannis E, Kandili A, Koutsianas C, Makris A, Georgiopoulos G, et al. Frequent conversion of tuberculosis screening tests during anti-tumour necrosis factor therapy in patients with rheumatic diseases. Ann Rheum Dis 2015;74:1848–53. Chen DY, Shen GH, Chen YM, Chen HH, Hsieh CW, Lan JL. Biphasic emergence of active tuberculosis in rheumatoid arthritis patients receiving TNFalpha inhibitors: the utility of IFNgamma assay. Ann Rheum Dis 2012;71:231–7. Singh JA, Furst DE, Bharat A, Curtis JR, Kavanaugh AF, Kremer JM, et al. 2012 update of the 2008 American College of Rheumatology recommendations for the use of disease-modifying antirheumatic drugs and biologic agents in the treatment of rheumatoid arthritis. Arthritis Care Res 2012;64:625–39. Acknowledgements: This study was supported by a grant of the Korean Health Technology R&D Project, Ministry for Health and Welfare, Republic of Korea (HI14C1774). Disclosure of Interest: None declared